Human embryos harbor complex mosaicism with broad presence of aneuploid cells during early development - Fan Zhai; Siming Kong; Shi Song; Qianying Guo; Ling Ding; Jiaqi Zhang; Nan Wang; Ying Kuo; Shuo Guan; Peng Yuan; Liying Yan; Zhiqiang Yan; et al. (Cell Discovery, 2024)
Abstract Pre-implantation genetic testing for aneuploidy (PGT-A) is used in approximately half of in vitro fertilization cycles. Given the limited understanding of the genetics of human embryos, the current use of PGT-A is based on biologically uncertain assumptions and unvalidated guidelines, leading to the possibility of disposing of embryos with pregnancy potential. We isolated and sequenced all single cells (1133) from in vitro cultured 20 human blastocysts. We found that all blastocysts exhibited mosaicism with mitotic-induced aneuploid cells and showed an ~25% aneuploidy rate per embryo. Moreover, 70% (14/20) of blastocysts contained ‘chromosome-complementary’ cells, suggesting genetic mosaicism is underestimated in routine PGT-A. Additionally, the analysis of 20,945 single cells from day 8–14 embryos (in vitro cultured) and embryonic/fetal organs showed that 97% of the analyzed embryos/organs were mosaic. Over 96% of their aneuploid cells harbored ≤ 2 chromosome errors. Our findings have revealed a high prevalence of mosaicism in human embryos.